WALKING STICK IMPLEMENTATION IN IMPROVING STUDENTS' UNDERSTANDING OF PAI SUBJECT IN SCHOOL - Akbar, Moh Ilham (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine: 1) The application of the talking stick in increasing students' understanding of PAI subjects at Paiton Islamic Middle School, 2. To find out the supporting and inhibiting factors for applying the talking stick in increasing student understanding of PAI subjects at Paiton Islamic Middle School. This study uses a qualitative research approach. At the same time, the type of field research (field research) is direct research in community or government institutions. Qualitative research or a qualitative approach is research to describe and learn more deeply about an activity, belief, thought, or perception of an individual or group